SOVIET AND POST-SOVIET RUSSIAN LANGUAGE LEXICAL-SEMANTIC CHANGES: THE RELATIONSHIP BETWEEN POLITICAL DISCOURSE AND LITERARY LANGUAGE - Khudaybergenova Nasiba Marimboevna (International Journal of Literature and Language Studies, 2026)
The present article examines the lexical-semantic transformations of the Russian language during the Soviet and post-Soviet periods, focusing on the intricate relationship between political discourse and literary language. The study analyzes how political ideology influenced the development of the Russian lexicon, the emergence of Soviet phraseology, and the subsequent adaptation of these linguistic phenomena in post-Soviet literary texts. The research methodology combines corpus linguistics approaches with discourse analysis, drawing on representative samples from Soviet and contemporary Russian literature. The findings demonstrate that political discourse has functioned as a powerful catalyst for lexical innovation, while literary language has simultaneously served as both a vehicle for ideological transmission and a medium of resistance through satirical and allegorical reinterpretation.